(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Recently, a protective effect of high myopia on the retina in diabetes has been reported; however, the mechanism of the interrelation between the elongation of axial length and the severity of diabetic complications in the retina is unclear. Purpose. To compare retinal changes in experimental type 2 diabetes melitus (T2DM) in animals with and without myopia as well as to determine the correlation betweeen axial length and anterior chamber depth of the eye and the severity of retinal disorders in DM. Material and Methods. Eyelids of two-week animals (30 rats) were sutured to induce axial myopia [12]. The animals were kept under poor light conditions for 14 days in order to achieve a higher rate of myopia [11, 13]. After a fortnight, the sutures were removed. After another fortnight, 15 rats with experimental myopia and 15 intact rats were modelled T2DM. T2DM was induced using 5 daily intraperitoneal injections of streptozotocin (15.0 mg per 1 kg). Control group comprised 10 intact rats which were kept under natural light condition for 14 days. All the animals were performed ultrasound scanning of the anterior segment to determine axial length (AL) and anterior chamber depth (ACL). A criterion of a diabetes onset was a blood glucose level of 4.5 mmol/l and above. The state of the retina was assessed ophthalmoscopically and expressed using a four-point scoring system. After two months, the animals were sacrificed under general anesthesia and the eyeballs were enucleated. Axial length was measured post mortem using a digital sliding caliper (Topex). Data obtained were processed using the non-parametric tests. Results. In experimental axial myopia, axial length increased by 20.5% compared with control. Experimental type 2 diabetes mellitus did not influence significantly on the axial length of the animals. In the rats with type 2 diabetes and deprivation myopia, axial length was significantly increased by 21.9% and by 19.4% as compared with control and the diabetic-only rats, respectively. Anterior chamber depth in the rats with type 2 diabetes mellitus and deprivation myopia was also increased compared with control. In experimental streptozotocin-induced type 2 diabetes mellitus, the diabetic rats with deprivation myopia had more pronounced changes in the retinal vessels as compared with the non-diabetic rats with deprivation myopia. A negative correlation was revealed between axial length values and the state of the retina in the diabetic rats with deprivation myopia (RSpearman = - 0.68, р<0.05); in a part of the animals, with an increase in axial length, the severity of the pathologic changes in the retina was less pronounced. Conclusion. In our experiment, the myopisation of the eyeball, including the elongation of axial length and the deepening of anterior chamber depth, is accompanied by a decrease of the signs of vascular disorders in the retina which are common for DM. This is also evidenced by the presence of a negative correlation between the myopisation of the eyeball and diabetes-associated disorders in the ocular fundus of the rats.